Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.20897/jisem.201812
|View full text |Cite
|
Sign up to set email alerts
|

Student Activity Analytics in an e-Learning Platfom: Anticipating Potential Failing Students

Abstract: The evolution of learning technology and tools changed the way students access information and build their knowledge. Registering the interaction of students with these tools generates a large amount of data that, once critically analysed, can provide important clues about the students' learning progress. Nevertheless research has still to be conducted to fully understand how (and if) the students' interaction with the learning technologies relates to their learning success. In parallel, new analytical tools m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…they were reading the materials more often. These results support the findings of Marques et al (2018), who had a similar observation that the most successful students were not the ones with the highest average access scores within the e-learning platform. Likewise, we can conclude that students with the best final results are more confident in their domain knowledge, resulting in less frequent access to the course materials provided in LMS.…”
Section: Discussionsupporting
confidence: 89%
“…they were reading the materials more often. These results support the findings of Marques et al (2018), who had a similar observation that the most successful students were not the ones with the highest average access scores within the e-learning platform. Likewise, we can conclude that students with the best final results are more confident in their domain knowledge, resulting in less frequent access to the course materials provided in LMS.…”
Section: Discussionsupporting
confidence: 89%
“…Internet activists recognize the high mobilizing potential of social networks, but they are confident that the authorities will try to control this. Also, a new generation of Internet users is recognized as rather apolitical [9][10][11][12][13]. The materials of all focus groups confirm the conclusions about the low level of youth's interest in discussing political issues on the Internet, which is related to the belief that it is impossible to change anything and the fear of sanctions, however, young people recognize many of the issues that are being actively discussed online.…”
Section: Resultssupporting
confidence: 63%
“…Real practice is a two-way communication: it is durable; there are endless stimulus reactions, prolonged in time. [10][11][12] Internet practices are one-way communication, users throw out their emotional intensity through posts, likes, reposts and comments, and stop there, i.e. in fact, they do not affect the immediate solution of social problems.…”
Section: Resultsmentioning
confidence: 99%
“…Nassar (2018) concluded that psychological empowerment is cognitive perception in which a person believes to be in a decisive position with worthy opinion in an organization. Psychological empowerment is a psychological understanding of an individual in which person perceives oneself with utmost power to remain in charge and in command in organization (Jordan et al, 2017;Marques et al, 2018). They debated in their research findings that psychological empowerment is a construct giving an employee the required strength of perception of being at governing role.…”
Section: Psychological Empowermentmentioning
confidence: 99%